Delayed on- and off-retinal responses of cones pathways in regular cannabis users: An On-Off flash electroretinogram case-control study. (April 2021) - Schwitzer, Thomas; Schwan, Raymund; Albuisson, Eliane; Bugin, Clarisse; Zech, Gaëlle; Angioi-Duprez, Karine; Bernardin, Florent; Laprévote, Vincent
Abstract: The retina is considered a useful area for investigating synaptic transmission abnormalities in neuropsychiatric disorders, including as a result of using cannabis, the most widely consumed illicit substance in the developed world. The impact of regular cannabis use on retinal function has already been evaluated, using pattern and flash electroretinogram (ERG) to demonstrate a delay in ganglion and bipolar cell response. Using multifocal ERG, it was showed that the delay to be preferentially located in the central retina. ERG tests do not separately examine the impact of cannabis on the On and Off pathways. The purpose of this study is to assess On and Off pathway function using On-Off ERG. We conducted an On-Off ERG test in 42 regular cannabis users and 26 healthy controls. The protocol was compliant with the International Society for Clinical Electrophysiology of Vision (ISCEV) standards. Amplitude and peak time were measured for the a-, b- and d-waves. Results in the regular cannabis users showed a significant increase in the latencies of both the b- and the d-wave (p = 0.020, p = 0.022, respectively, Mann-Whitney U test), with no change in the wave amplitudes. A-wave peak time and amplitude were unchanged. These findings are reflective of an effect of regular cannabis use on the On and Off pathways and are consistent with previous findings which also identified increases in retinal neuron response times. We confirm here that regular cannabis use impacts the post-receptoral cones pathway at the level of bipolar cells, affecting the On and Off pathways. Highlights: An On-Off ERG test was conducted in both regular cannabis users and healthy controls. Cannabis users showed an increase in the latencies of the b- and d-wave. These findings show an effect of cannabis use on the On and Off pathways.